Intra-Household Dynamics and the Design of Social Protection Programs : The Case of Polygamous Households in North Burkina Faso - Guilbert, Nathalie (World Bank, Washington, DC, 2016)
A recent overview of World Bank social safety net programs and gender highlighted the need for greater consideration of intra-household dynamics in the design of social protection programs (Bardasi 2014). During program design, decisions have to be made about who to target, how much and how often to give cash transfers, and what measures should accompany cash transfers. These decisions become even more complex in the context of polygamous households. The conclusions above are meant to illustrate important links between intra-household dynamics and the design of cash transfer programs. As a preliminary study, this research did not capture the actual effects of cash transfers. It is important to remember that money received from the government in the form of a regular cash transfer may be treated differently than income from other sources. Additional research is planned that will measure differences in the use of cash transfers depending on the social protection program design.